Mental Health Literacy and Stress of Nurses in Government Hospitals - Jaimook, Kingkarn; Skulphan, Sombat; Thapinta, Darawan; Suvanayos, Chalinee (Journal of Phrapokklao Nursing College, Chanthaburi, 2024)
This descriptive correlational research aimed to examine the relationship between mental health literacy and stress of nurses in government hospitals. The samples were 415 nurses working in government hospitals in health region 1. The research instruments included a demographic data questionnaire, the Mental Health Literacy Scale with a reliability of .78, and the Nurse Stress Assessment Questionnaire with a reliability of .96. Data were collected from March to June 2021. Statistics used for data analysis included frequency, percentage, mean, standard deviation, and Pearson’s product moment correlation. The research results revealed that the nurses in government hospitals demonstrated overall mean score of mental health literacy at a high level (M = 3.73, SD = .35) and overall mean score of stress at a moderate level (M = 3.01, SD = .71). In addition, there was no relationship between mental health literacy and stress of nurses in government hospitals. This research suggests that nurses should assess their stress periodically in order to obtain information for proper stress management.